2016
DOI: 10.1063/1.4940938
|View full text |Cite
|
Sign up to set email alerts
|

A bead-based fluorescence immunosensing technique enabled by the integration of Förster resonance energy transfer and optoelectrokinetic concentration

Abstract: Bead-based immunosensing has been growing as a promising technology in the point-of-care diagnostics due to great flexibility. For dilute samples, functionalized particles can be used to collect dispersed analytes and act as carriers for particle manipulation. To realize rapid and visual immunosensing, F€ orster resonance energy transfer (FRET) was used herein to ensure only the diabetic biomarker, lipocalin 1, to be detected. The measurement was made in an aqueous droplet sandwiched between two parallel plate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…This is useful method for complex proteomics studies and biomedical studies to identify potential target protein for various applications. [31][32][33][34]…”
Section: Discussionmentioning
confidence: 99%
“…This is useful method for complex proteomics studies and biomedical studies to identify potential target protein for various applications. [31][32][33][34]…”
Section: Discussionmentioning
confidence: 99%
“…The fluorescence intensity of the microbeads was enhanced as they are concentrated by REP. We previously showed that microbead manipulation is a function of electrical frequency. 20,24,34 In this study, the optimal manipulation of 3 μm microbeads by REP was realized with 15 V pp at 35 kHz and 12 mW laser intensity. The fluorescence of the microbeads dynamically aggregated under the operating conditions was excited and emitted through a filter cube equipped in the microscope.…”
Section: Optoelectrokinetic Platform and Microbead Manipulationmentioning
confidence: 99%
“…In the present study, a non-invasive immunosensing technique ( Fig. 1) based on an optoelectrokinetic platform, termed rapid electrokinetic patterning (REP), [19][20][21][22][23][24] was used to manipulate immunocomplexed microbeads for the detection of DR biomarkers in tear samples. We utilized a colloidal suspension containing microbeads conjugated with capture and free suspending fluorescence tagged probe antibodies.…”
Section: Introductionmentioning
confidence: 99%
“…Particle concentration had been done adopting the optoelectrokinetic technique, termed rapid electrokinetic patterning (REP). 1,2 With an electric field and a focused laser beam applying on the microchip simultaneously, the immunocomplexes in the droplet of sample were further concentrated to enhance the F€ orster resonance energy transfer (FRET) fluorescent signal. 2 This approach is relative complicated and the rising of temperature might damage the analytes.…”
Section: Introductionmentioning
confidence: 99%